Tantangan Thaharah di Era Modern - Irfiqna Dinana; Oktavia Bulan Dwi Sabrina; Annisa Prima; Ahmad Mu’is (Qolamuna : Jurnal Studi Islam, 2025)
Examines the problems faced in the application of thaharah (purification) in the midst of progress and modernization. In the context of everyday life, many individuals neglect the importance of thaharah, which is a key requirement in performing acts of worship, such as prayer. This article highlights the challenges posed by outside cultural influences that often contradict Islamic values, including a decline in awareness of physical and spiritual hygiene. The article explores how globalization and modernization can lead to a loss of cultural identity and Islamic values. The author also emphasizes the need for public education on thaharah to improve understanding and practice of proper purification. The article also illustrates the benefits of thaharah in creating a healthy and clean society, as well as the importance of maintaining traditional values in the face of challenging times. Thus, the implementation of thaharah is expected to strengthen individual morals and ethics in social interactions and maintain environmental cleanliness as part of efforts to build Islamic civilization in the modern era. Keywords : purification, implementation, modern